REDUPLIKASI SEMANTIS DALAM PEMBENTUKAN KATA BAHASA REMPUNG KAJIAN PERSPEKTIF DIAKRONIS - Muzianti, Yeni; Mahsun, Mahsun; Sukri, Muhammad (Universitas Islam Negeri Mataram, 2024)
The study investigates semantic reduplication in the Rempung language, aiming to elucidate its forms, functions, and meanings. Employing a qualitative descriptive approach, the research gathers data in the form of words or phrases that exhibit semantic reduplication. Data analysis methods include introspection and the speech method, encompassing direct and indirect speech, note-taking, and recording. With a diachronic perspective, the research utilizes the intralingual Equivalence method, employing both basic and advanced comparison techniques. The analysis results are presented formally and informally. The study draws upon the Simatupang theory and identifies seven forms of semantic reduplication across three categories. Semantic reduplication in the Rempung language serves two functions: inflection and derivation, each carrying nuanced meanings